The influence of 8,786 Western China kindergarten teachers' emotional intelligence on work engagement - Zhang, Zedong; Li, Yan; Wang, Ye; An, Xiaomin (Frontiers in Psychology, 2025)
Although emotional intelligence (EI) has been shown to influence work engagement significantly (WE) in many professions, the relationship between EI and WE among kindergarten teachers in Western China remains underexplored. This study aims to fill this gap by investigating how the EI of kindergarten teachers affects their WE and whether educational background moderates this relationship. A sample of 8,786 kindergarten teachers completed the Emotional Intelligence Scale for Kindergarten Teachers and the Work Engagement Scale. The results indicate that EI is positively correlated with and predictive of WE among kindergarten teachers. However, within the internal structure of EI, emotional perception does not predict WE, while emotional identification negatively predicts it. Furthermore, the educational background of kindergarten teachers was found to moderate the relationship between EI and WE. To enhance WE among kindergarten teachers in the future, it is crucial to view EI as a developable skill. This can be accomplished by providing teachers with diverse social practice opportunities and offering structured EI training programs.